Evaluation by Surface EMG of a Dysphagia Rehabilitation Maneuver, “Soba Slurping-Like Training”, Using a Feeding Tube - HAYASHI, Yoshihiko; KOYAMA, Zenya; YAMAGUCHI, Taiki; MATSUSHITA, Shinko; OI, Kumiko; HIRATA, Akiko; YAMAMI, Yumiko; HISAMATSU, Noriko; ISHITOBI, Shingo (The Japanese Journal of Dysphagia Rehabilitation, 2012)
We developed a dysphagia rehabilitation maneuver, “soba slurping-like training”, using a feeding tube, suitable for elderly persons and patients with limited neck movement. The aim of the present study was to evaluate the effect of this maneuver on submental muscles, infrahyoid muscles, and sternocleidomastoid muscle, by comparing EMG activity when performing this maneuver and traditional maneuvers such as “Shaker Exercise” and “Mendelsohn Maneuver”.Surface EMG was measured from 16 normal subjects with an average age of 22.2 years old in three muscle groups.The original EMG signals while performing the “soba slurping-like training” maneuver or other traditional ones were smoothed with a time constant of 100 ms by the RMS （root mean square） method. To compare EMG activity between maneuvers, mean values of %MVC for each individual in each muscle group were measured and were statistically analyzed using one-way analysis of variance and multiple comparison of Bonferroni. In submental muscles, the mean value of %MVC of the “soba slurping-like training” maneuver was as high as that of “Shaker Exercise”, and in infrahyoid muscles was two-thirds of that of “Shaker Exercise”. On the other hand, in the sternocleidomastoid muscle, the EMG activity of the “soba slurping-like training” maneuver was significantly low compared with “Shaker Exercise”. In conclusion, we consider that “soba slurping-like training” is an effective dysphagia rehabilitation maneuver for elderly persons and patients with limited neck movement.